1996
DOI: 10.1063/1.116904
|View full text |Cite
|
Sign up to set email alerts
|

Plasma beam deposited amorphous hydrogenated carbon: Improved film quality at higher growth rate

Abstract: High quality diamondlike a-C:H has been deposited, at low ion bombardment energies, from an expanding thermal argon/acetylene plasma at high growth rate. It is observed that quality improvement, in terms of hardness, is equivalent to maximization of the refractive index. The highest refractive indices are obtained when the admixed acetylene flow and the argon ion flux emanating from the plasma source are comparable in magnitude, which suggests critical loading. This also indicates that the acetylene has to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 17 publications
5
41
1
Order By: Relevance
“…The plasma self-bias is also negligible; as the electron temperature is low ͑Ϸ0.2 eV͒ the self-bias is in the order of 1 V. 26 Furthermore, we have found that the highest hardness values are obtained when the residual argon-ion density, and thus ionization degree, in front of the growing film is minimal. 26,27 Modification of the film growth by an energetic ion bombardment thus seems not necessary to obtain diamondlike material. Concerning the hardness results it is evident that both the FIG.…”
Section: Resultsmentioning
confidence: 99%
“…The plasma self-bias is also negligible; as the electron temperature is low ͑Ϸ0.2 eV͒ the self-bias is in the order of 1 V. 26 Furthermore, we have found that the highest hardness values are obtained when the residual argon-ion density, and thus ionization degree, in front of the growing film is minimal. 26,27 Modification of the film growth by an energetic ion bombardment thus seems not necessary to obtain diamondlike material. Concerning the hardness results it is evident that both the FIG.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Using an expanding thermal plasma deposition rates up to 75 nm/s have been obtained without loss of material quality. The material properties even improve at increasing growth rate 14,16 and the films exhibit diamondlike quality.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Using an expanding thermal plasma deposition rates up to 75 nm/s have been obtained without loss of material quality. The material properties even improve at increasing growth rate 14,16 and the films exhibit diamondlike quality. 15 Variation of the plasma settings and the subsequent change in material properties is obtained by varying the ionization degree of the expanding plasma and the admixed acetylene precursor flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar setup was used in the past to deposit hydrogenated amorphous carbon at high rates. 27 Background gas is sampled from the plasma by a Balzers QMS 200 Prisma residual gas analyzer ͑RGA͒ through an orifice of 100 m. The RGA is pumped by a turbopump (60 l /s), positioned directly under the quadrupole. The operating pressure during measurements is in the 10 Ϫ6 mbar range, depending on the chamber pressure.…”
Section: Methodsmentioning
confidence: 99%